People’s Multiparty Democracy: Digital Challenges and Democratic Adaptation in Nepal - Pandey, Surendra Prasad (State, Society and Development: PMPD Perspectives, 2026)
People’s Multiparty Democracy (PMPD), introduced by Madan Bhandari and adopted by the Communist Party of Nepal (Unified Marxist–Leninist) in 1993, represents one of the most distinctive ideological innovations in modern Nepali political thought. By proposing “people’s democratic state power” in place of “people’s democratic dictatorship,” the doctrine reconciles Marxist political goals with competitive multiparty democracy, grounding legitimacy in popular participation. However, since PMPD’s formulation in the early 1990s, the global political economy has been immensely transformed by the rise of digital capitalism, social media, and artificial intelligence—developments that have fundamentally reshaped political communication, electoral behavior, and democratic governance. This study analyzes the historical evolution of PMPD and evaluates its relevance in the contemporary digital environment. Drawing Platform capitalism Digital democracy Introduction on qualitative historical analysis and political theory, it examines PMPD’s emergence in the context of Nepal’s democratic struggles and the global crisis of socialism following the collapse of the Soviet Union, and explores the implications of network society, platform capitalism, surveillance capitalism, algorithmic governance, and digital disinformation for democratic politics in Nepal. The study argues that PMPD must expand beyond its traditional emphasis on electoral democracy and political pluralism to incorporate digital governance, data sovereignty, and algorithmic accountability—adaptations necessary to preserve democratic legitimacy and ensure the resilience of political institutions in the age of artificial intelligence.